2019
DOI: 10.1111/nmo.13766
|View full text |Cite
|
Sign up to set email alerts
|

Hypoganglionosis in the gastric antrum causes delayed gastric emptying

Abstract: Background Enteric nervous system (ENS) abnormalities have been implicated in delayed gastric emptying but studies exploring potential treatment options are limited by the lack of an experimental animal model. We examined the ENS abnormalities in the mouse stomach associated with aging, developed a novel model of gastroparesis, and established a new approach to measure gastric emptying. Methods A modified gastric emptying assay was developed, validated in nNOS −/− mice, and tested in mice at multiple ages. Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The number of these neurons differs depending on animal species, the segment of the GI tract and the type of enteric ganglia studied 20 , 25 29 . Moreover, in most cases, including the mouse stomach, the population of nitrergic enteric neurons is relatively numerous 20 , 28 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The number of these neurons differs depending on animal species, the segment of the GI tract and the type of enteric ganglia studied 20 , 25 29 . Moreover, in most cases, including the mouse stomach, the population of nitrergic enteric neurons is relatively numerous 20 , 28 31 .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown successful isolation and expansion of ENSCs from mouse and human intestine and demonstrated their ability to engraft and differentiate into neurons and glial cells following allotransplantation or xenotransplantation into mouse models of enteric neuropathies 8 , 10 , 16 , 21 , 36 . These observations serve as proof of concept that cell therapy can be a promising therapeutic approach to replace missing or damaged enteric neurons to restore GI function 4 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…ey found that the number of nerve fibers in the round and longitudinal muscle layers was normal in sections from patients with well controlled DM, while the number of nerve fibers in patients with poorly controlled DM decreased by 40-50%. Baker et al [39] established an ENS absorption model by local ablation of the anterior gastric antrum in mice. Delayed gastric emptying of solid and liquid was observed in the model mice, which was thought to be directly related to the loss of neurons.…”
Section: Discussionmentioning
confidence: 99%